Fixed Bed Adsorption of Drugs on Silica Aerogel from Supercritical Carbon Dioxide Solutions. (23rd June 2013) - Caputo, Giuseppe
Abstract : Supercritical adsorption coupled with the high adsorption capacity of silica aerogel allows the preparation of a new kind of delivery systems of poor water soluble drugs. In order to overcome drawbacks of conventional techniques where the use of liquid solvents can cause the fracture of aerogel porous structure, in this work a new adsorption process of drugs from a supercritical mixture is proposed. Adsorption takes place from a fluid solution of the drug in supercritical CO2 and ethanol as cosolvent. A fixed bed adsorption plant has been developed to allow fast mixing of fluid phase and effective contact in the adsorption column. The use of ethanol as cosolvent allows to overcome the limitation of supercritical adsorption due to low solubility of many drugs in supercritical CO2 . Adsorption isotherms were measured for one-model substance, nimesulide, at 40°C, and breakthrough curve was experimentally obtained. The drug loading of the drug into silica aerogel was up to 9 wt%. The drug composite was characterized using scanning electron microscopy, and release kinetics of the adsorbed drug were also evaluated by in vitro dissolution tests. The dissolution of nimesulide from loaded aerogel is much faster than dissolution of crystalline nimesulide. Around 80% of nimesulide dissolves from the aerogel within 6 minutes, whereas dissolving 80% of the crystalline drug takes about 90 min.